ANALISIS PEMILIHAN SUPPLIER PUPUK NPK DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Shinta Wahyu Hati; Nelmi Sabrina Fitri (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract : Supplier selection is a chain in supply chain management. Supplier selection is one of the most important things in purchasing activity for the company. Companies should be selective in choosing suppliers because the right supplier selection will support the output of the company. This research was   conducted   at   oil   palm  agribusiness   company  which   will   develop cooperative relationship with NPK fertilizer supplier. The purpose of this study is to select the best NPK fertilizer suppliers that meet the company's criteria. The criteria specified in choosing NPK fertilizer suppliers are cost, quality, delivery  and  service.  While  the  suppliers  who  have  worked  with  PT  ABC Batam are suppliers X, supplier Y and supplier Z. This research uses AHP method assisted with expert choice v.11 software. From the assessment of the importance of criteria in the selection of suppliers, cost criteria get the highest weight of 0.452, then followed by the quality criteria with weight 0.234, service criteria with weight 0.163 and delivery criteria with weight 0.151. For supplier score starting from supplier X get highest weight 0.528, supplier Y with weight0.325 and supplier Z with weight 0.148